2002
DOI: 10.1046/j.1365-2958.2002.02745.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of haemoglobin with the Neisseria meningitidis receptor HpuAB: the role of TonB and an intact proton motive force

Abstract: SummaryWe have characterized the interaction of the Neisseria meningitidis TonB-dependent receptor HpuAB with haemoglobin (Hb). Protease accessibility assays indicated that HpuA and HpuB are surface exposed, HpuB interacts physically with HpuA, and TonB energization affects the conformation of HpuAB. Binding assays using [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
71
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(79 citation statements)
references
References 92 publications
7
71
1
Order By: Relevance
“…In those experiments, wildtype HpuAB saturably bound 125 I-Hb with a moderate affinity approximately 50-fold lower than that of the interaction of Tf with the TbpAB receptor (15,69). We did not detect significant Hb binding to mutant strains lacking either HpuA, HpuB, or both receptor components by using that assay or a solidphase dot blot analysis (69). Based on those observations, we concluded that both HpuA and HpuB were required to bind and to utilize Hb.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…In those experiments, wildtype HpuAB saturably bound 125 I-Hb with a moderate affinity approximately 50-fold lower than that of the interaction of Tf with the TbpAB receptor (15,69). We did not detect significant Hb binding to mutant strains lacking either HpuA, HpuB, or both receptor components by using that assay or a solidphase dot blot analysis (69). Based on those observations, we concluded that both HpuA and HpuB were required to bind and to utilize Hb.…”
mentioning
confidence: 78%
“…No known homologues of HpuA exist in public databases, and its role in HpuAB function remains to be determined. We have reported data suggesting that HpuA and HpuB physically interact to form a functional receptor complex (51,69). Characterization of isogenic single mutants of HpuA and HpuB suggested that both receptor components are absolutely required for the utilization of Hb or HbHp (48,69).…”
mentioning
confidence: 99%
See 3 more Smart Citations